Improving Quality and Reducing Work Obstacles by Using Geographic Information Systems (GIS) - Ali , Luma Essam (International Journal of Psychosocial Rehabilitation, 2020)
Abstract: The research aims to identify how to use geographic information systems to improve quality. (23) Projects were selected as a sample for research, which are exploratory projects carried out by the seismic teams of the Iraqi Oil Exploration Company. Research problem is determined by the existence of work obstacles that affect negatively the productivity of work and have a major influence on the progress of production, stoppage of work, slow completion, inaccuracy and loss of effort. This problem was identified practically by applying the Deming Circle to improve the quality and use of quality tools. Work obstacles were classified as natural, technical, security, governmental and social obstacles, and to solve this problem, geographic information systems (GIS) programs has been used. Moreover, building database was used to represent spatial and descriptive data in the form of maps using ArcGIS 10.8 and to study the impact of improvement by spatial analysis of work sites. The researcher discovered several results, the most important outcome was the possibility of using geographic information systems in building database that can be referred to when making decisions and help in solving various problems associated with exploration work.